The Concept of Administrative Matter - Timotijevic, Djordje (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
Among the unresolved issues not only in the positive legal regulation of administrative procedure but also within the broader scope of administrative law, both on a theoretical and practical level, a particularly significant place is occupied by the concept of administrative matter and its precise definition. Administrative matter represents one of the most frequently debated concepts in administrative law. Legal theorists offer various definitions and interpretations of this term, while its precise determination has also posed a challenge for legislators. Indeed, in comparative law, it is rare to encounter legal systems that provide an explicit definition of the administrative matter, and the domestic legislature introduced such a definition for the first time only in 2009, within the Law on Administrative Disputes.This paper analyzes the concept of administrative matter from the standpoint of legal theory, as well as comparative and domestic legislation. It then proceeds to present the author’s own views regarding the definition and elements of the administrative matter, both in the context of administrative procedure and administrative dispute.The aim of the paper is to highlight, through observations and conclusions drawn from various theoretical and legislative perspectives, the diversity of interpretations surrounding this concept. Furthermore, it seeks to propose a uniform definition of administrative matter from the perspective of administrative procedure and administrative dispute, and to point out the distinction between administrative matter and administrative-judicial matter, a category that should be regulated separately within the framework of administrative procedural law.